Associations between grandparental involvement and psychological outcomes in adolescents facing family adversity - Westwood, Sarah Anne (Department of Psychology, 2016)
With an increase in life expectancy, there is greater potential for grandparents to be involved in the lives of their grandchildren. The aim of this study was to investigate whether grandparental involvement was related to fewer negative psychological outcomes (i.e. peer, emotional, hyperactivity and conduct problems), and whether this association remained as a protective effect when adolescents faced high levels of family adversity. A cross--‐sectional study consisting of 536 Black and Coloured adolescents (ages 13--‐15 years) from two schools located in the greater Cape Town area was conducted. The results of bivariate and SEM analyses demonstrated that grandparental involvement was associated with a reduction in the presence of all negative psychological outcomes, which shows that grandparental involvement can play a compensatory role in adolescents' lives. The results of a path analysis indicated that grandparental involvement only has a protective effect for reducing peer problems for female adolescents who are experiencing high levels of family adversity. No other association between grandparental involvement and negative psychological outcomes was significant when the adolescent was facing high levels of family adversity. Together the results of this study suggest that grandparental involvement can have a positive effect in adolescents' lives, and therefore future research should move beyond simply looking at an adolescent's immediate family as a source of support.